Evaluating the Impact of BAZNAS's “Lumbung Pangan” Program on Farmer Welfare: A Case Study in Barito Kuala Using the CIBEST Approach - Maulida, Sri; Lestari, Haifa; Saleh, Muhammad; Saipudin; Rakhmatullah, Akhsanul (GoAcademica Research & Publishing, 2024)
This study evaluates the impact of the 'Lumbung Pangan' program by BAZNAS on the welfare of 56 zakat-receiving farmers in Barito Kuala, South Kalimantan. The program provided agricultural guidance and training on organic fertilizer production, aiming to increase rice productivity and shift to organic farming practices. Using the CIBEST approach, we assessed changes in the material and spiritual welfare of farmers after program implementation in August. Results show that 24 farmers achieved Quadrant I (welfare), 28 fell into Quadrant III (materially poor), and only 1 remained in Quadrant IV (totally poor), with no farmers in Quadrant II (spiritually poor). These findings highlight the potential of zakat-based initiatives to enhance agricultural productivity and quality of life in rural communities.